2018
DOI: 10.1097/01.naj.0000530941.11737.1c
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Wound Care to Family Caregivers

Abstract: : This article is part of a series, Supporting Family Caregivers: No Longer Home Alone, published in collaboration with the AARP Public Policy Institute. Results of focus groups, conducted as part of the AARP Public Policy Institute's No Longer Home Alone video project, supported evidence that family caregivers aren't given the information they need to manage the complex care regimens of family members. This series of articles and accompanying videos aims to help nurses provide caregivers with the tools they n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 18 publications
2
12
0
1
Order By: Relevance
“…In the present study, ICGs with an education level lower than high school were significantly more likely to have a low level of T2D-related knowledge compared with ICGs with other educational levels; thus, priority should be given to these ICGs when designing interventions in the community. This supports recent studies by Kirkland et al [ 28 ] and Silva et al [ 29 ], where people with higher levels of education are more receptive to health education campaigns. In addition, higher education can also lead to more accurate health beliefs and knowledge, and thus lead to better lifestyle choices, better skills as well as greater self-advocacy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, ICGs with an education level lower than high school were significantly more likely to have a low level of T2D-related knowledge compared with ICGs with other educational levels; thus, priority should be given to these ICGs when designing interventions in the community. This supports recent studies by Kirkland et al [ 28 ] and Silva et al [ 29 ], where people with higher levels of education are more receptive to health education campaigns. In addition, higher education can also lead to more accurate health beliefs and knowledge, and thus lead to better lifestyle choices, better skills as well as greater self-advocacy.…”
Section: Discussionsupporting
confidence: 91%
“…Spouse caregivers are particularly vulnerable, often because of older age, low education, lower income and social isolation [ 17 ]. Access to systematic and easy-to-follow training is therefore crucial for the well-being of ICGs and the effectiveness of the care they are providing [ 18 ]. In our study, the majority of ICGs reported a lack of knowledge on caregiving activities.…”
Section: Discussionmentioning
confidence: 99%
“…When patients are discharged from hospital to home, there are expectations for family members, when possible, to be caregivers. Therefore, both patients and family caregivers need education about changing wound dressings to optimize their skills, recognize abnormal conditions, and alleviate fear (Kirkland‐Kyn et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The social support offered by ICGs also creates a feeling of acceptance and high level life satisfaction among persons with diabetes-related foot problems [ 25 ]. However, it has been identified that majority of ICG fear making mistakes and found tasks such as wound dressing to be emotionally challenging and indicated that they needed training to be effective at home [ 26 ]. Despite some of the known evidence of the active role ICGs can play in DFU care, a systematic review indicated that from 1995 to 2013, only 1% of publications in the literature mentioned ICGs as members of the wound care team [ 27 ].…”
Section: Introductionmentioning
confidence: 99%